Utilization of Fun Games as Earthquake Disaster Mitigation Efforts for Inclusive Children - Haikal Muhammad Ihsan; Dias Pratami Putri; Hurry Mega Insani; Armandha Redo; Alnidi Safarach Bratanegara (Tunas Geografi, 2022)
The lembang fault is active and can potentially trigger earthquakes in the West Bandung Regency area and its surroundings. The lembang fault has two segments, namely the western and eastern segments, with a movement of 3 mm/year. The Ngamprah Raya Special School (SLB) is a school for children with special needs located in the Lembang fault area in the western segment. This condition causes SLB Ngamprah Raya to be in an earthquake-prone area. One of those affected is highly vulnerable to earthquakes, namely children, even more vulnerable, namely children with special needs or inclusion. Children with special needs need education regarding the Lembang fault earthquake and earthquake disaster mitigation. Earthquake disaster mitigation learning based on fun games needs to be done for Children with Special Needs. The purpose of this study is to utilize fun game media for earthquake disaster mitigation education for children with special needs. The method used is participatory observation involving accompanying teachers and students. The sample used is accidental sampling. The study results show that the fun game of snakes and ladders based on disaster mitigation is effective and efficient for children with special needs with mental retardation. In its implementation, game time and participants must be considered and limited to achieve learning. Students get developmental achievements as expected by going through three cycles. Each cycle is carried out with an effective and efficient snake and ladders game adjustment scheme. Learners are more likely to be able to capture interactive material. Snakes and ladders fun game can be an alternative solution in developing earthquake disaster mitigation learning media for mental retardation.Keywords: Fun game, Disaster Mitigation, Children with Special Needs.